2015
DOI: 10.1002/chem.201405947
|View full text |Cite
|
Sign up to set email alerts
|

Hot‐Hole Extraction from Quantum Dot to Molecular Adsorbate

Abstract: Ultrafast thermalized and hot-hole-transfer processes have been investigated in CdSe quantum dot (QD)/catechol composite systems in which hole transfer from photoexcited QDs to the catechols is thermodynamically favorable. A series of catechol derivatives were selected with different electron-donating and -withdrawing groups, and the effect of these groups on hole transfer and charge recombination (CR) dynamics has been investigated. The hole-transfer time was determined using the fluorescence upconversion tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 31 publications
(78 citation statements)
references
References 55 publications
7
70
1
Order By: Relevance
“…It is clear from Figure A, B that the luminescence decay traces of CdS and CdSe QDs are much faster with CAT and NCAT as compared to pure QDs decay. This faster luminescence decay in the presence of CAT and NCAT can be attributed to the hole‐transfer process from QDs to CAT and NCAT as mentioned above and also described earlier . It is interesting to see from Figure A, B that the emission kinetics decay trace is much faster in QDs/NCAT composite system as compared to QDs/CAT composite although −Δ G HT ° value for hole–transfer reaction is less in the former as compared to the latter.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…It is clear from Figure A, B that the luminescence decay traces of CdS and CdSe QDs are much faster with CAT and NCAT as compared to pure QDs decay. This faster luminescence decay in the presence of CAT and NCAT can be attributed to the hole‐transfer process from QDs to CAT and NCAT as mentioned above and also described earlier . It is interesting to see from Figure A, B that the emission kinetics decay trace is much faster in QDs/NCAT composite system as compared to QDs/CAT composite although −Δ G HT ° value for hole–transfer reaction is less in the former as compared to the latter.…”
Section: Resultssupporting
confidence: 72%
“…have studied the charge separation in zinc porphyrin–QD complexes where they have shown electron transfer from zinc porphyrins to QDs. In our earlier investigations we also demonstrated ultrafast charge separation in binary systems of CdSe and CdS QDs with different molecular adsorbates . In all the above stated reports different molecules were chosen that acts as either hole‐ or electron‐transporting molecules for QDs with an aim to get better charge separation.…”
Section: Introductionmentioning
confidence: 99%
“…The bleaching recovery kinetics in femtosecond TA for the CdSe/4NP composite becomes much faster than that of CdSe QDs (at the same time, the bleaching intensity decreases drastically), whereas for CdSe/4MP the bleaching recovery kinetics becomes slower. [23,[63][64][65] In addition, in our earlier investigation, [52] we observed in CdSe/p-methoxycatecholt hat the paramethoxy moiety introduces as trong electron-donating ability, which makes the molecule easy to oxidize, and thus, it acts as as trong hole-accepting molecule. [67] They observedt hat BQ rapidly quenched electrons from the CB of CdSe QDs with the formation of as hortlived CT state, with al ifetime of 2.7 ps, which resulted in faster bleaching recovery kinetics.…”
Section: Ultrafast Ta Studiesmentioning
confidence: 83%
“…[52] Recently,A livisatos et al reported that, upon changing the substituent from electron donating to withdrawing, the rate of hole transfer could be tuned from CdSe/CdS to different ferrocened erivatives. [52] Recently,A livisatos et al reported that, upon changing the substituent from electron donating to withdrawing, the rate of hole transfer could be tuned from CdSe/CdS to different ferrocened erivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation